Honduras : Second Reviews Under the Stand-By Arrangement and the Arrangement Under the Standby Credit Facility-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Honduras' Second Review Under the Stand-by Arrangement (SBA) and the Arrangement under the Standby Credit Facility (SCF). All 2015 end-June performance criteria and indicative targets were met, most with significant margins. On the structural side, June and September 2015 benchmarks were broadly observed. The revised program proposed for 2016 envisages a further strengthening of fiscal and net international reserve targets. The authorities are pressing ahead with structural reforms, including the introduction of a Fiscal Responsibility Law, an overhaul of tax administration, and reforms to the Honduran Social Security Institute. Based on performance to date and the authorities' updated intentions and commitments, the IMF staff recommends completion of the second review under the SBA/SCF arrangement.